Mapeamento das áreas de ocorrências do caramujo africano (Achatina fulica) na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The introducing process of a new specie, in an external environment to its geographic origin, can initiate its spread, through the absence of natural predators and favoring a conducive environment to their survival. This introduction, can happen through economic ways, when the native specie is replaced by another, searching for a greater commercial productivity, or even accidentally, by goods’ transport or displacement of people. From that, the native species can be extinct, intensifying the economic prejudices and aggravating the public health problems. In this way, the presents dissertation had as objective, study the biogeographic features of the specie Achatina Fulica on urban environment of Manaus City, likewise to identify its biogeographic cycle and its relation with biotic and abiotic factors. Was added to these objectives the Achatina Fulica’s spatial distribution mapping, therefore, identifying the areas of Manaus City and the Geotopic units where was registered the mollusk presence. The methodological approach of this search includes: the bibliographic survey to the theoretical reference, the observation and field collections for obtaining data and georeference of geotope types. Furthermore, were performed morphometric measurements and elaboration of thematic maps. The results evidenced a mapping with 126 occurrence points on 32 neighborhood in Manaus city, where it was possible identifying the geotopics features, with active mollusk predominance, on solid waste deposit, urban forestry fragments edges, river banks, wastelands, steep slope. The normalized difference vegetation index by (NDVI), prove the close mollusk relation with environments of urban forestry fragments, where the vegetal cover that serves as a shelter, in the hottest periods of the year. The density of the specie in the city, was represented by the use and applicatition of the Kernel Map, that showed the Central South Zone being the highest populacional density. Can be incorporated into this result, that the geomorphological unit most wanted by A. Fulica to your shelter, reffered to the lands located on a 20.7 meter level curve, near of rivers and canals, corresponding to the areas subject to periodic flooding. However, was also registered the occurrence of theses individuals, in altimetric dimensions of 55 meters, being associated to the existence of this environment with the springs and forestry fragments. The annual climatic data shows the favoring of the specie survival through the following temperature indices of 28°C, relative umidity of 80% and pluviometric precipitation of 17mm. The mophometric features relative to the shell lenght, studied over one year period in 1.855 individuals, inffered that the Achatina fulica population in Manaus city is ranked as a young individuals population. However, it’s worth mentioning, that the other factores, can be related to the high density areas of mollusk population, like food availability and possible predators, undetected, that can have important effects over the populacional dynamic, regulating the growth rates and in the preferences for certain areas of Manaus city.
Keywords: Caramujo gigante africano; Gastrópodes; Achatina fulica; Biogeografia; População biológica; CIENCIAS HUMANAS; Achatina fulica; Manaus; Geótopos; Biogeografia